Learner agency in a problem-based learning curriculum: A qualitative study on perspectives of undergraduate dental students - Nidhi Gupta; Sruthi Sunil; Kamran Ali; Trine Fink; Xiangyun Du (PLoS ONE, 2026)
Learner agency (LA), a student’s ability to take ownership of their learning and make purposeful decisions, is increasingly recognized as a critical competency in preparing adaptable healthcare professionals. While LA has been explored in general education, its development within dental education, particularly in the context of problem-based learning (PBL), remains underexplored. This qualitative study investigated undergraduate dental students’ perceptions of how a PBL curriculum supports the development of LA. Using purposive sampling, Year 2 and 3 students enrolled in a PBL-based dental program were invited to participate in focus group discussions conducted between September 2024 and March 2025. Four audio-recorded sessions were transcribed verbatim and analyzed thematically using a combined deductive-inductive approach with MAXQDA software. Twenty-two students participated in the study. Findings revealed that PBL supported key elements of LA, including enhanced motivation, self-efficacy, knowledge acquisition, goal setting, and reflective practices. Peer collaboration and facilitator guidance were identified as important enablers. However, challenges such as workload intensity, time management difficulties, and uneven peer participation were perceived as barriers to fully exercising agency. Overall, participants viewed PBL as a valuable foundation for fostering LA in dental education. Addressing structural and contextual barriers may further optimize its impact and better support the development of autonomous, self-regulated learners.